(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This study examines the difference in perceptions on the seven dimensions of e-book selection practices between male and female respondents; between respondents of different age groups; between respondents of different grades; between respondents of different educational levels; and between respondents of different years of service (duration of service). Questionnaires were distributed to 150 professional librarians who dealt with e-book in Malaysian academic libraries. The seven dimensions were resource sharing, accessibility, support distance education, sustainability, collection features, cataloging e-structure, and user friendliness. The finding indicates that female respondents had better perceptions on resource sharing and support distance education than male respondents; that respondents in the youngest age group (21-29 years) had a poorer perception of collection features and user friendliness than those from the other two age groups; that perceptions on e-book selection practices were the same regardless of respondents’ grades, levels of education and duration of service.